(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article analyzes some problematic aspects of the current legislation in improving the taxation system of business entities in the Republic of Uzbekistan and develops proposals for their elimination. The main attention in the study is paid to the need for the stability of tax legislation, further improvement of simplified tax regimes, legal strengthening of digital tax administration, and the introduction of a system for assessing the effectiveness of tax benefits. The article analyzes the application of the current "Tax Code" and related by-laws to business entities, and considers the problems encountered in practice - in particular, the high tax burden, irregular distribution of benefits, complexity of reporting, and lack of clarity in some norms. The results of the study will serve to further effectively implement state policy to improve the tax system in Uzbekistan and support entrepreneurial activity.